Proteins homologous to aquaporins of higher plants in the freshwater alga Ulothrix zonata (Ulotrichales, Chlorophyta). Issue 1 (2nd January 2016) - Permyakov, Aleksey; Osipova, Svetlana; Bondarenko, Nina; Obolkina, Lyubov; Timoshkin, Oleg; Boedeker, Christian; Geist, Birgit; Schäffner, Anton R.
Abstract : The green filamentous alga Ulothrix zonata inhabits Lake Baikal and overgrows the underside of hummocky ice during winter and spring. To clarify physiological adaptations of U. zonata to low temperature and the potential contribution of membrane water permeabilities, the expression level of aquaporins from a winter population growing under the lake ice and in interstitial water was compared with that of benthic summer and autumn populations of algae by immuno-detection using an anti-maize PIP1 (plasma membrane intrinsic protein) antiserum. Algal, and in particular Ulvophycean, transcriptome sequences are only partially available and this higher plant-specific PIP1 epitope has not been detected so far in available genomic datasets. PIP1 expression levels were highest in the ice population and the rise in water temperature during summer was correlated with a drop in PIP1 amounts, which slightly increased again in autumn. ITS2 rDNA (internally transcribed spacer region 2) sequences revealed conspecificity of the ice and summer populations. The difference in PIP1 aquaporin expression suggests adaptation of the algae to changing environments by maintaining membrane permeability at low temperatures. Our study shows that the ice population of U. zonata inhabiting Lake Baikal is a unique subject for studying physiological and biochemical adaptation mechanisms of freshwater extremophiles.